2014
DOI: 10.5455/jice.20140826030222
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study, antifungal activity, phytochemical screening and total phenolic content of Algerian Aristolochia longa

Abstract: Aim:Aristolochia longa (from the family Aristolochiaceae) is widely used in Algerian traditional medicine. Here, we document ethnomedicinal uses by local population of Mascara province (West Algeria) and we evaluate the antifungal activity, the phytochemical composition and total phenolic content of aqueous extract (decoction) of the roots of A. longa from Algeria.Materials and Methods:The ethnobotanical investigation was carried out in Mascara Province (West Algeria). Antifungal activity was assessed against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In the same study, phenolic content of A indica root extract was determined as 54.27 ± 0.77 mg GAE/g extract . For the aqueous extract, the total phenolic content of A longa of was found to be 6.07 ± 0.12 mg GAE/g dry plant, for methanol extract, 132.33 ± 3.77 μg GAE/mg dry plant, and for acetone extract 525.43 ± 29.6 μg GAE/mg dry plant…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the same study, phenolic content of A indica root extract was determined as 54.27 ± 0.77 mg GAE/g extract . For the aqueous extract, the total phenolic content of A longa of was found to be 6.07 ± 0.12 mg GAE/g dry plant, for methanol extract, 132.33 ± 3.77 μg GAE/mg dry plant, and for acetone extract 525.43 ± 29.6 μg GAE/mg dry plant…”
Section: Resultsmentioning
confidence: 78%
“…found to be more effective than ABRME (EC 50 : 130.76 µg/mL). 12,47 Besides, Benmehdi and Behilil reported that activity of A clematitis root methanol extract was 0.142 mg/mL. 23 Das et al 54 The source of the diseases caused by oxidative stress is the free radicals formed by transition metal ions in living systems.…”
Section: Antioxidant Activity Of Extractsmentioning
confidence: 99%
“…Previously, Djeridane et al, reported the following results from roots methanol extract of Aristolochia longa L. 4 : total phenolics 1.47±0.02 mg GAE/g dw, flavonoids content 0.81±0.02 mg RE/g dw, flavonols content 0.41±0.002 mg QE/g dw, and also in other studies 33 , total phenolic content in A. longa aqueous extract of roots was found to be 6.07 ± 0.12 mg GAE/g, but our extract contain higher levels, this could be explained by the change of the plot location.…”
Section: Flavonoids Contentmentioning
confidence: 93%
“…The amount of oxalic acid in leaves of C. urens per 100 g was estimated using the regression equation ΔA = 0.966C -0.027, where C is the concentration of oxalic acid in mg/ml and ΔA is Ab-As (Table 2﴿. www.wjpr.net Phenolic compounds have redox properties, which allow them to act as antioxidants, as their free radical scavenging ability is facilitated by their hydroxyl groups. [21] Terpenes play an important role as signal and growth regulators of plants. Since, terpenoids promote glutathione s-transferase and cell apoptosis, they have been used for their anti-cancer properties.…”
Section: Estimation Of Phenol Terpenoids and Oxalic Acid Contentmentioning
confidence: 99%
“…The activity of C. urens could be attributed due to presence of terpenoids, phenols and saponins. [30] [31] The mechanism of inhibition by terpenoids involves membrane disruption by the lipophilic compounds. Phenols are effective against bacteria and fungi because they inhibit enzymes by the oxidized compounds possibly through reactions with sulfhydryl group or through more non-specific interactions with proteins.…”
Section: Pseudomonas Sp Escherichia Coli Bacillus Subtilis and Stamentioning
confidence: 99%